Epitaxial Ferroelectric Hf0.5Zr0.5O2 with Metallic Pyrochlore Oxide Electrodes. Issue 10 (2nd February 2021) - Zhang, Zimeng; Hsu, Shang‐Lin; Stoica, Vladimir A.; Paik, Hanjong; Parsonnet, Eric; Qualls, Alexander; Wang, Jianjun; Xie, Liang; Kumari, Mukesh; Das, Sujit; Leng, Zhinan; McBriarty, Martin; et al.
Abstract: The synthesis of fully epitaxial ferroelectric Hf0.5 Zr0.5 O2 (HZO) thin films through the use of a conducting pyrochlore oxide electrode that acts as a structural and chemical template is reported. Such pyrochlores, exemplified by Pb2 Ir2 O7 (PIO) and Bi2 Ru2 O7 (BRO), exhibit metallic conductivity with room‐temperature resistivity of <1 mΩ cm and are closely lattice matched to yttria‐stabilized zirconia substrates as well as the HZO layers grown on top of them. Evidence for epitaxy and domain formation is established with X‐ray diffraction and scanning transmission electron microscopy, which show that the c ‐axis of the HZO film is normal to the substrate surface. The emergence of the non‐polar‐monoclinic phase from the polar‐orthorhombic phase is observed when the HZO film thickness is ≥≈30 nm. Thermodynamic analyses reveal the role of epitaxial strain and surface energy in stabilizing the polar phase as well as its coexistence with the non‐polar‐monoclinic phase as a function of film thickness. Abstract : Metallic pyrochlore oxide electrodes are introduced to create epitaxial Hf0.5 Zr0.5 O2 thin films. The emergence of the non‐polar‐monoclinic phase from the polar‐orthorhombic phase is observed when the film thickness is ≥≈30 nm. Further tuning through such an epitaxial stabilization process can lead to the orthorhombic phase being stable over an even larger thickness range.